Given the equation
![7(x-5)=2x-10](https://img.qammunity.org/2023/formulas/mathematics/college/c08bymdfliyw1q5ljnaxv7t96gpg3zll4a.png)
First step solve the term in the parenthesis by applying the distributive propperty of mutiplication that states that if you have a(b+c)→ab+ac
![\begin{gathered} 7(x-5)=2x-10 \\ 7x-35=2x-10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qiplmf7zctq21plusto45nrkqkat1pbjty.png)
Next pass all x-related terms to one side of the equation and the others to the other side:
![\begin{gathered} 7x-35=2x-10 \\ 7x-2x=-10+35 \\ 5x=25 \\ x=(25)/(5) \\ x=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5oeoptcjs4usica1vz6xwcx4689xila94c.png)
x=5